Diverse macroscopic helical motions of microribbons driven by electrons. Issue 17 (13th February 2017) - Peng, Cheng; Zhang, Yifan; Zhang, Yibin; Zhou, Zichao; Che, Yanke; Zhao, Jincai
Abstract : Diverse macroscopic helical motions of microribbons driven by electrons arise from the combination of diagonal in-plane and vertical non-bonded distortions. Abstract : Novel stimuli-responsive microscale materials capable of undergoing diverse out-of-plane helical motions ( e.g., bending, twisting and coiling) when exposed to electron irradiation are reported. The macroscopic morphological changes of microribbons induced by electrons arise from the combination of diagonal in-plane, non-bonded distortion relative to the long axis of the microribbon and vertical non-bonded distortion.